Farm Investment and Adoption of Fixed Milk Price Contracts on Irish Dairy Farms - Shefali Pardeshi; Jason Loughrey; Declan O'Connor (German Journal of Agricultural Economics (GJAE), 2024)
After the milk quota removal in 2015, the Irish dairy industry has expanded dramatically. Various economic, social and environmental considerations are part of farmer's choice to invest and to expand. This study evaluates selected factors contributing to recent dairy farmer's investment decisions and examines the relationship between the adoption of Fixed Milk Price Contracts as a risk management tool and farm investments. This research applies the two-stage residual inclusion approach to address this research question using Teagasc NFS data from 2016 to 2021. This approach is applied to control for potential endogeneity including risk aversion. The results point to the economic relevance of the FMC adoption towards farm investment decisions although the magnitude of the association is limited. Subsidies play an important role in the investment decision although they are a small proportion in the overall specialised dairy farm income and provide a relatively stable source of income in Ireland. We finally conclude that, there is scope to improve the design of these FMCs in terms of protecting farmers from drastic margin volatility and to increase the adoption rate
Keywords: 330; Dairy Farm Investment; Contract Farming; Fixed Milk Price Contracts; Risk Management; 2SRI Approach